Floodplain forests drive fruit-eating fish diversity at the Amazon Basin-scale - Sandra Bibiana Correa; Karold V. Coronado-Franco; Celine Jézéquel; Amanda Cantarute Rodrigues; Kristine O. Evans; Joshua J. Granger; Hans ter Steege; Iêda Leão do Amaral; Luiz de Souza Coelho; Florian Wittmann; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; et al. (Proceedings of the National Academy of Sciences, 2025)
Unlike most rivers globally, nearly all lowland Amazonian rivers have unregulated flow, supporting seasonally flooded floodplain forests. Floodplain forests harbor a unique tree species assemblage adapted to flooding and specialized fauna, including fruit-eating fish that migrate seasonally into floodplains, favoring expansive floodplain areas. Frugivorous fish are forest-dependent fauna critical to forest regeneration via seed dispersal and support commercial and artisanal fisheries. We implemented linear mixed effects models to investigate drivers of species richness among specialized frugivorous fishes across the ~6,000,000 km 2 Amazon Basin, analyzing 29 species from 9 families (10,058 occurrences). Floodplain predictors per subbasin included floodplain forest extent, tree species richness (309,540 occurrences for 2,506 species), water biogeochemistry, flood duration, and elevation, with river order controlling for longitudinal positioning along the river network. We observed heterogeneous patterns of frugivorous fish species richness, which were positively correlated with floodplain forest extent, tree species richness, and flood duration. The natural hydrological regime facilitates fish access to flooded forests and controls fruit production. Thus, the ability of Amazonian floodplain ecosystems to support frugivorous fish assemblages hinges on extensive and diverse seasonally flooded forests. Given the low functional redundancy in fish seed dispersal networks, diverse frugivorous fish assemblages disperse and maintain diverse forests; vice versa, diverse forests maintain more fish species, underscoring the critically important taxonomic interdependencies that embody Amazonian ecosystems. Effective management strategies must acknowledge that access to diverse and hydrologically functional floodplain forests is essential to ensure the long-term survival of frugivorous fish and, in turn, the long-term sustainability of floodplain forests.